2020
DOI: 10.1016/j.obmed.2020.100190
|View full text |Cite
|
Sign up to set email alerts
|

Potentially preventable urinary tract infection in patients with type 2 diabetes – A hospital-based study

Abstract: Aim: To investigate the prevalence of urinary tract infections in hospitalized patients with type 2 diabetes mellitus and identify corresponding risk factors. Methods: We conducted a cross-sectional study on 7.347 patients with type 2 diabetes mellitus as the principal diagnosis, using hospitalization discharge summary data from January 1 to December 31, 2015. Disease stages were classified as stages 1, 2, and 3. Results: Of 7.347 patients, 16.2% had urinary tract infections. The urinary tract infection preval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…With increasing age, the risk of developing UTI in both sexes, especially in women, increases. For example, in the Carrondo study, the UTI rate in people aged 18–64 was 9%, compared with 27.5% in people over 85 years old [ 27 ]. In all of the articles reviewed, the UTI rate in women was higher than in men, which appears to be related to bladder neurological dysfunction, physiological bladder changes due to aging or shortness of breath, and proximity to the anus among women [ 24 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With increasing age, the risk of developing UTI in both sexes, especially in women, increases. For example, in the Carrondo study, the UTI rate in people aged 18–64 was 9%, compared with 27.5% in people over 85 years old [ 27 ]. In all of the articles reviewed, the UTI rate in women was higher than in men, which appears to be related to bladder neurological dysfunction, physiological bladder changes due to aging or shortness of breath, and proximity to the anus among women [ 24 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study by Carrondo 2020 in Portugal found that 23.6% of women with type 2 diabetes had UTI, compared to only 10.5% of men with type 2 diabetes [ 27 ]. A 2011 study in Fu2014 [ 11 ] reported a 14% increase in UTI incidence in women with type 2 diabetes and 9.1% in non-diabetic women, compared with 5% in men with type 2 diabetes and 2.4% in non-diabetic men.…”
Section: Discussionmentioning
confidence: 99%
“…With increasing age, the risk of developing UTI in both sexes, especially in women, increases. For example, in the Carrondo2020 study, the UTI rate in people aged 18-64 was 9%, compared with 27.5% in people over 85 years old [27]. In all of the articles reviewed, the UTI rate in women was higher than in men, which appears to be related to bladder neurological dysfunction, physiological bladder changes due to aging or shortness of breath and its proximity to the anus among women [24,27].…”
Section: Discussionmentioning
confidence: 99%
“…For example: In Carrondo2020 study, the prevalence rate of UTI in diabetic patients was Stage1, 24.4% and in diabetic patients Stage2, was 4.8% [27].Living geography appears to be associated with urinary tract infections in patients with type 2 diabetes. In an epidemiological study, the prevalence rate was highest in developing countries (24%) and 12.9% and 19.6% in the United States and Europe, respectively [62].…”
Section: Examplementioning
confidence: 92%
See 1 more Smart Citation